Nanotechnology Based Approaches in Phage Therapy: Overcoming the Pharmacological Barriers - Kaur, Sandeep; Kumari, Anila; Kumari Negi, Anjana; Galav, Vikas; Thakur, Shikha; Agrawal, Manish; Sharma, Vandana (Frontiers in Pharmacology, 2021)
With the emergence and spread of global antibiotic resistance and the need for searching safer alternatives, there has been resurgence in exploring the use of bacteriophages in the treatment of bacterial infections referred as phage therapy. Although modern phage therapy has come a long way as demonstrated by numerous efficacy studies but the fact remains that till date, phage therapy has not received regulatory approval for human use (except for compassionate use).Thus, to hit the clinical market, the roadblocks need to be seriously addressed and gaps mended with modern solution based technologies. Nanotechnology represents one such ideal and powerful tool for overcoming the pharmacological barriers (low stability, poor in-vivo retention, targeted delivery, neutralisation by immune system etc.) of administered phage preparations.In literature, there are many review articles on nanotechnology and bacteriophages but these are primarily focussed on highlighting the use of lytic and temperate phages in different fields of nano-medicine such as nanoprobes, nanosensors, cancer diagnostics, cancer cell targeting, drug delivery through phage receptors, phage display etc. Reviews specifically focused on the use of nanotechnology driven techniques strictly to improve phage therapy are however limited. Moreover, these review if present have primarily focussed on discussing encapsulation as a primary method for improving the stability and retention of phage(s) in the body.With new advances made in the field of nanotechnology, approaches extend from mere encapsulation to recently adopted newer strategies. The present review gives a detailed insight into the more recent strategies which include 1) use of lipid based nano-carriers (liposomes, transfersomes etc.) 2) adopting microfluidic based approach, surface modification methods to further enhance the efficiency and stability of phage loaded liposomes 3) Nano- emulsification approach with integration of microfluidics for producing multiple emulsions (suitable for phage cocktails) with unique control over size, shape and drop morphology 4) Phage loaded nanofibers produced by electro-spinning and advanced core shell nanofibers for immediate, biphasic and delayed release systems and 5) Smart release drug delivery platforms that allow superior control over dosing and phage release as and when required. All these new advances are aimed at creating a suitable housing system for therapeutic bacteriophage preparations while targeting the multiple issues of phage therapy i.e., improving phage stability and titers, improving in-vivo retention times, acting as suitable delivery systems for sustained release at target site of infection, improved penetration into biofilms and protection from immune cell attack. The present review thus aims at giving a complete insight into the recent advances (2010 onwards) related to various nanotechnology based approaches to address the issues pertaining to phage therapy. This is essential for improving the overall therapeutic index and success of phage therapy for future clinical approval.